Application of network pharmacology in traditional Chinese medicine for the treatment of cardiac diseases - Zhai, Xi; Chen, Xingyu; Xiao, Xiao; Wu, Lan (Frontiers in Pharmacology, 2025)
Many innovative traditional Chinese medicines (TCMs) play a significant role in cardioprotection against cardiac diseases by addressing the basic causes of heart attack, which presents as a dual deficiency of qi and yang. Network pharmacology, offering a multi-dimensional perspective, can elucidate the specific mechanisms of the active components of TCM via a system pharmacology strategy. The methodology of network pharmacology is highly consistent with the modernization of TCM and provides a new perspective and theoretical basis for both basic research and its supplementary clinical research on cardiac diseases. This review summarizes the steps, databases, and software used in network pharmacology systematically. It also discusses the current achievements in applying network pharmacology to understand the mechanisms of some important TCMs (Huangqi, Renshen, and Danshen) and their active components in the context of cardioprotection against cardiac diseases based on a comprehensive literature search on PubMed. Anti-inflammation, anti-oxidation, anti-apoptosis, anti-pyroptosis, and regulation of the PI3K–AKT–mammalian target of the rapamycin (mTOR) signaling pathway were identified as the main mechanisms through which these TCMs exert cardioprotective effects. In addition, this approach provides new ideas for the cure of cancer-induced cardiac injury through network pharmacology.